Justice and Legal Certainty in Case of Novel Baswedan - Tatang, Leonando S. (Universitas Negeri Gorontalo, 2025)
This study aims to determine justice and legal certainty in the case of Novel Baswedan. The legal research used in this paper is normative legal research using statutory and case approaches. Furthermore, using the technique of analysis of legal materials Interpretation. The study results show that the Novel Baswedan Persecution Case, Seen from the Perspective of Justice and Legal Certainty, is applied to Court Decision Number 372/Pid.B/2020/PN.Jkt.Utr. It has many irregularities, as is the case with the application of articles that do not have clear legal certainty or the application of articles that are not following what the defendant did. From a justice point of view, the public prosecutor's indictment did not reflect a sense of justice for the victim, where the defendant should have been subject to premeditated serious maltreatment. However, the public prosecutor was only subject to ordinary maltreatment. All stakeholders within the scope of law enforcement, including the police, public prosecutors, legal advisors, and judges, must represent the values and legal norms that apply to create legal certainty and justice for people who are dealing with legal proceedings, both as perpetrators and victims in general.